S25 Improved lung cancer survival following low dose computed tomography (LDCT) screening in asbestos-exposed individuals. (12th November 2019) - Harris, EJA; Franklin, P; Reid, A; Olsen, N; de Klerk, NH; Musk, AW; Brims, FJH
Abstract : Introduction: Asbestos exposure is recognised to raise the risk of lung cancer (with additive synergism combined with a tobacco smoking history). A significant asbestos-exposure history is not adequately considered in any current US lung cancer screening guidelines. The Western Australian (WA) Asbestos Review Program (ARP) has screened nearly five-thousand asbestos-exposed individuals for asbestos-related diseases since 1990, using annual chest x-ray (CXR), and latterly LDCT following the publication of the high-profile 'National Lung Screen Trial' in 2011. The hypothesis that LDCT screening improves lung cancer survival in this population was examined. Subjects and methods: Participants with significant asbestos exposure, (≥ 3 months full-time occupational exposure or pleural plaque on chest imaging), had attended at least one ARP appointment and were diagnosed with lung cancer between 2007 and 2017. The diagnosis was confirmed through data linkage from the WA state cancer registry (performed mid-2015) or diagnosis through LDCT screening. Participants were classified into three groups: 1. Not under active follow-up - between 1/1/2007 and 01/01/2012 (no imaging or appointments within prior 15 months of diagnosis) 2. CXR screening - between 1/1/2007 and 1/1/2012 (CXR within the prior 15 months) 3. LDCT screening - between 1/9/2012 and 1/9/2017 (LDCT scan within prior 15 months) Survival time from diagnosis was calculated. The date of censor for groups 1 and 2 was 1/1/2012 and for group 3 was 1/9/2017 allowing a 5-year period to be considered for all three groups. Cox proportional-hazards model was used to investigate all-cause mortality by group. Results: Table 1 shows group demographics and cancers detected. Compared to the reference group (Group 1), after adjustment for age and sex, an 82% mortality risk reduction was demonstrated in the LDCT screening group (HR 0.18, 95% CI 0.06–0.54, p=0.002). No significant difference in risk was shown between the CXR screening and reference group (HR 0.70, 95% CI 0.34–1.44, p=0.36). Conclusion: Improved lung cancer survival was demonstrated in those diagnosed by LDCT screening. Extending consideration of LDCT screening to those with an appropriate asbestos-exposure history may improve mortality from lung cancer, however, the correct population for cost-effective screening has yet to be well defined.